2013
DOI: 10.1177/1457496913490610
|View full text |Cite
|
Sign up to set email alerts
|

Closure of skin incision after thyroidectomy through a supraclavicular approach: a comparison between tissue adhesive and staples

Abstract: Background: The objective of this study was to compare the effectiveness and cosmetic results of tissue adhesive or surgical staples in thyroidectomy through a supraclavicular incision.Methods: This was a prospective, randomized study of consecutive patients undergoing thyroidectomy by a supraclavicular approach. Eligible patients were randomized into two groups: one group had the incision closed with tissue adhesive (the experimental group) and the other with surgical staples (the control group). The main out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…One paper by Guarino et al was a retrospective cohort study. Three studies compared staples vs glue; three papers compared sutures vs staples; two papers compared suture vs steri‐strips; and two papers compared sutures vs glue . A total of 742 patients were included in this review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One paper by Guarino et al was a retrospective cohort study. Three studies compared staples vs glue; three papers compared sutures vs staples; two papers compared suture vs steri‐strips; and two papers compared sutures vs glue . A total of 742 patients were included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…With regards to surgical procedure, all but one, Vinay et al, included a description of the procedure performed, although to varying detail. Five papers described platysma closure, and four papers described subcutaneous closure prior to skin/epidermal closure. Pronio et al reported the use of ceftriaxone as prophylactic antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study Yang YL et al, these patients were randomly divided into two groups (one experimental and one control group) of 70 patients each. 12 In the process of the study, 8 patients were excluded because of intraoperative findings. Therefore, there were 65 patients in the experimental group (tissue adhesive) and 67 patients in the control group (surgical staples).…”
Section: Discussionmentioning
confidence: 99%